Enhancing students' self-efficacy and creativity in computer numerical control machining through peer-assisted project-based learning - Sutopo Sutopo; Bayu Rahmat Setiadi; Irdayanti Mat Nashir; Virda Hersy Lutviana Saputri; Achmad Arifin; Tri Adi Prasetya; Chrisna Tri Harjanto; Beni Tri Sasongko (Jurnal Pendidikan Vokasi, 2024)
The demand for increasingly diverse product designs and specifications in the manufacturing industry requires  Computer Numerical Control (CNC) machine operators to have high technical skills and strong self-efficacy and creativity. High self-efficacy allows operators to be more confident in applying their technical skills, while creativity helps them solve problems and challenges during the production process. This study aims to improve students' self-efficacy and creativity by applying the Peer-Project Based Learning (Peer-PjBL) model, which combines aspects of project-based learning with peer-to-peer learning. The method used in this research is Classroom Action Research (PTK), which consists of two implementation cycles. Each cycle involves planning, implementation, observation, and reflection stages. The subjects of this study were 20 students who took the CNC Machining Technology course at Universitas Negeri Yogyakarta. Data were collected using a questionnaire that measured self-efficacy and student creativity indicators and then analyzed descriptively. The results showed that applying the Peer-PjBL method significantly increased students' self-efficacy and creativity in each research cycle. This improvement can be seen in students' ability to face new challenges independently, as well as their ability to generate diverse creative ideas in solving problems. This research makes an important contribution to the development of learning methods in vocational education by emphasizing the improvement of technical abilities and non-technical skills, such as self-efficacy and creativity, which are needed in the modern world of work.